The burden of frailty in heart failure: Prevalence, impacts on clinical outcomes and the role of heart failure medications - Hsi‐Yu Lai; Shih‐Tsung Huang; Stefan D. Anker; Stephan vonHaehling; Masahiro Akishita; Hidenori Arai; Liang‐Kung Chen; Fei‐Yuan Hsiao (Wiley, 2024)
Abstract Background Frailty often coexists with heart failure (HF), which significantly aggravates the clinical outcomes of older adults. However, studies investigating the interplay between frailty and HF in older adults are scarce. We aimed to assess the prevalence of frailty using the cumulative deficit approach and evaluate the impacts of frailty on health utilization, use of HF‐related medications and adverse clinical outcomes (all‐cause mortality, all‐cause readmissions and HF readmissions) among older HF patients. Methods A total of 38 843 newly admitted HF patients were identified from Taiwan's National Health Insurance Research Database and categorized into three frailty subgroups (fit, mild frailty and severe frailty) based on the multimorbidity frailty index. Cox regression models and Fine and Gray subdistribution hazard models were used to estimate the impacts of frailty on clinical outcomes at 1 and 2 years of follow‐up. Generalized estimating equation models were further conducted to evaluate the associations between longitudinal and time‐varying use of HF‐related medications and clinical outcomes among distinct frailty subgroups. Results Of 38 843 older HF patients (mean age 80.4 ± 8.5 years, 52.3% females) identified, 68.3% were categorized as frail (47.5% of mild frailty and 20.8% of severe frailty). The median number of readmissions (fit: 1 [inter‐quartile range-IQR 2], mild frailty: 1 [IQR 2] and severe frailty: 2 [IQR 3]) increased with the severity of frailty. Only 27.3% of HF patients died of cardiovascular diseases regardless of their frailty status. Compared with the fit group, the severe frailty group was associated with increased risk of all‐cause mortality (adjusted hazard ratio 1.16, 95% confidence interval [CI] 1.11-1.21), all‐cause readmissions (subdistributional hazard ratio (sHR) 1.21, 95% CI 1.16-1.25) and HF‐related readmissions (sHR 1.14, 95% CI 1.09-1.20) at 2 years of follow‐up. Those who used triple or more HF‐related medications were at lower risk for all‐cause readmissions (adjusted odds ratio [aOR] 0.49, 95% CI 0.44-0.54) and HF‐related readmissions (aOR 0.42, 95% CI 0.37-0.47) at 2 years of follow‐up even in the severe frailty group. Conclusions Frailty is highly prevalent and associated with increased risk of all‐cause mortality, all‐cause readmissions and HF readmissions among older HF patients. Those who were using triple or more HF‐related medications were at lower risk of adverse clinical outcomes across distinct frailty subgroups. Further studies are needed to optimize the treatment strategies for older HF patients with distinct frailty status.